Specific gravity of pinang tree (Areca catechu) according to height level / Noor Fairuz Kamaruddin - Kamaruddin, Noor Fairuz (2006)
The study of specific gravity was performing on Areca catechu. Specific gravity was determined using maximum moisture content method. The samples were analyzed from five levels of tree- base, 20 %, 40 %, 60 %, and 80 % from height level of tree. The result indicated that specific gravity is high at the portion of 80 % from height level of tree while the base has the lowest value of specific gravity. The specific gravity for another three portion is decrease with the increase in height level of tree.